Effect of soliton interaction on timing jitter in communication systems - Pinto, Armando N. (2012)
Timing jitter in soliton communication systems is studied, taking into account both soliton interaction and amplifier noise, Deviations from Gordon-Haus jitter for closely spaced solitons are observed. A new analytical model for the timing jitter is proposed, The model presented considers interaction in a random sequence of solitons and the effect of the amplified spontaneous emission noise added in each amplification stage, We obtain a good agreement between the new analytical model and simulation results for practical communication systems.